2016
DOI: 10.1177/1028315316662980
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perceived Risk and Risk Reduction Strategies in the Pursuit of Higher Education Abroad

Abstract: While past studies have merely focused on perceived risks that influence how students select the destination of international education best suited to their needs, research on perceived risk regarding post-purchase behavior remains limited. This study attempts to extend and redefine the perceived risk paradigm by uncovering the underlying elements of perceived risk among international students who are studying in Malaysian universities. Furthermore, it seeks to explore how demographic factors and risk reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
11
0
2
Order By: Relevance
“…In particular students within this age group are more likely to be enrolled in bachelors and/or higher degree programs, this shows that cost factor is an important factor prior enrollment. This outcome validates the findings of Lam et al (2016) in Malaysia. The authors found that the price of education and cost of living influence decisions of international students, their sample has similar profile in terms of age with the current study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In particular students within this age group are more likely to be enrolled in bachelors and/or higher degree programs, this shows that cost factor is an important factor prior enrollment. This outcome validates the findings of Lam et al (2016) in Malaysia. The authors found that the price of education and cost of living influence decisions of international students, their sample has similar profile in terms of age with the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Such students often possess higher level of global mindedness compared to other learners (McGladdery and Lubbe, 2017) and are more likely to get hired by international firms. In similar vein, social referrals from friends, relatives and social circles seems to be a vital motivator as it reduce students' perceptions of risk (Lam et al, 2016). Moreover, political ties with host country is important in terms of ideology and policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the administration of the questionnaires, in-depth face-to-face interviews were conducted to confirm that the measures for those constructs were adequate and comprehensive for the Malaysia travel destination context. A random sample of 20 international travellers was interviewed and only items identified by more than six respondents (or 20%) were included in the questionnaire for further analysis ( Lam, Tong, & Ariffin, 2017 ). The scales were also revised for content validity by three prominent scholars who are experts in the destination marketing field.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it would be useful to consider the risk impact associated with travelling, given the current global environment, as this may influence their perceptions towards their overall higher edutourism experience. These constructs are proven to be key factors that contribute towards valued travel experiences in tourism and hospitality studies, (Ariffin et al, 2018; Lam, Tong et al, 2017; Mansour and Ariffin, 2017).…”
Section: Limitations and Future Research Recommendationsmentioning
confidence: 99%